On Incest : Psychoanalytic Perspectives. - Ambrosio, Giovanna (Psychoanalysis & women series, 2005)
The collection deals with a number of issues that surround incest, including Freud's work and how his outlook changed throughout the years, the post-Freudian theories, treatment of both offender and victim through traditional one-on-one and group therapy, the importance of the sex of the analyst, the permeations of the abuser/abused, and the "why" of incest. As well as addressing theory, the papers include moving and at times disturbing clinical vignettes to provide an insight into clinical practice.